2003
DOI: 10.1007/s00299-003-0617-6
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated large-scale transformation of wheat (Triticum aestivum L.) using glyphosate selection

Abstract: An Agrobacterium-mediated transformation system with glyphosate selection has been developed for the large-scale production of transgenic plants. The system uses 4-day precultured immature embryos as explants. A total of 30 vectors containing the 5-enol-pyruvylshikimate-3-phosphate synthase gene from Agrobacterium strain CP4 (aroA:CP4), which confers resistance to glyphosate, were introduced into wheat using this system. The aroA:CP4 gene served two roles in this study-selectable marker and gene of interest. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(20 citation statements)
references
References 39 publications
(47 reference statements)
1
18
0
1
Order By: Relevance
“…These ratios were higher than those of other reports and indicated that the transformation treatments adopted here generated transgene insertions at more loci than previously reported. For example, Khanna and Daggard (2003) demonstrated that 35% of transgenic lines showed 3:1 segregation ratios, whereas Hu et al (2003) reported 46% of 3:1 ratios. Analysis of 26 plants revealed single gene copies in 35% of the lines tested, two or three copies in 50%, and four to five copies in only 15% (Cheng et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ratios were higher than those of other reports and indicated that the transformation treatments adopted here generated transgene insertions at more loci than previously reported. For example, Khanna and Daggard (2003) demonstrated that 35% of transgenic lines showed 3:1 segregation ratios, whereas Hu et al (2003) reported 46% of 3:1 ratios. Analysis of 26 plants revealed single gene copies in 35% of the lines tested, two or three copies in 50%, and four to five copies in only 15% (Cheng et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant progress in Agrobacterium transformation of wheat ( Triticum aestivum L.) in recent years, but it is still confined mainly to a few responsive varieties with quite different transformation frequencies such as the model spring genotype ‘Bobwhite’ (Cheng et al , 1997, 2003; Hu et al , 2003), other spring wheat varieties, Fielder, Cadenza, and Veery 5 (Weir et al , 2001; Khanna and Daggard, 2003; Wu et al , 2003; Jones et al , 2005), and the winter wheat variety Florida (Wu et al , 2003; Jones et al , 2005). Efficient Agrobacterium -mediated transformation of wheat via in planta inoculation was reported by Risacher et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Roundup Ready wheat with herbicide resistance was developed with this technique15. Improved transformation efficiency was achieved by using a super expression vector and adding polyamine compounds to co-cultivation media1617. Desiccation treatment of infected wheat tissues during co-culturing was found to enhance the transformation efficiency of T-DNA18.…”
Section: Discussionmentioning
confidence: 99%
“…Until very recently, transformation methodologies for cereals such as wheat (Weeks et al 1993;Cheng et al 1997), maize (Frame et al 2000) and sorghum (Able et al 2001) have been somewhat inefficient. The utilisation of Agrobacterium and better in vitro selection strategies have substantially improved the efficiency and reliability of transformation in sorghum (Gao et al 2005), maize (Frame et al 2002) and wheat (Hu et al 2003). The techniques used are not the focus of this review, and readers are referred to Curtis (2004) for comprehensive methodologies.…”
Section: Introductionmentioning
confidence: 98%